Composition-driven spin-reorientation transition in ferromagnetic alloy films - Dittschar, Armin; Zharnikov, Michael; Kuch, W.; Lin, M.-T.; Schneider, C.M.; Kirschner, J. (Physical review. B, Condensed matter and materials physics, 1998)
A spin-reorientation transition upon a variation of the Fe concentration x is observed in ultrathin fcc FexCo1−x alloy films on Cu(001) for x>77%. For film thicknesses below 4 monolayers the magnetic easy axis changes from in-plane on the Co-rich side to out-of-plane on the Fe-rich side. Since no structural transitions accompany this spin-reorientation transition, varying the alloy composition can be interpreted as varying the number of 3d electrons. Upon changing the average d-band filling by as little as 0.1 electron strong changes of the anisotropy energy are observed.
Gesehen am 06.02.2023